Employment Status and Countermeasures for Chinese Language Majors - Chen, Shiming (International Journal of Global Economics and Management, 2024)
This paper provides an in-depth analysis of the current employment situation of Chinese majors and puts forward corresponding countermeasures. By sorting out the employment profiles, employment fields and challenges faced by Chinese language graduates, it is found that there is a prominent contradiction between the supply and demand of Chinese language graduates, changes in the demand for vocational skills as well as a disconnect between education and actual demand. In view of these problems, this paper puts forward countermeasures and suggestions for education reform and innovation, vocational skills improvement and broadening employment channels. It is hoped that these suggestions can provide certain reference and inspiration for the educational reform of Chinese language majors and the employment of graduates.